Biomaterials in Orthopaedics and Bone Regeneration Design and Synthesis - Bains, Preetkanwal Singh; Sidhu, Sarabjeet Singh; Bahraminasab, Marjan; Prakash, Chander; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on the recent advances in the field of orthopaedic biomaterials, with a particular emphasis on their design and fabrication. Biomimetic materials, having similar properties and functions to that of the natural tissue, are becoming a popular choice for making customized orthopaedic implants and bone scaffolds. The acceptability of these materials in the human body depends on the right balance between their mechanical and biological properties. This book provides a comprehensive overview of the state-of-the-art research in this rapidly evolving field. The chapters cover different aspects of multi-functional biomaterials design, and cutting-edge methods for the synthesis and processing of these materials. Advanced manufacturing techniques, like additive manufacturing, used for developing new biomimetic materials are highlighted in the book. This book is a valuable reference for students and researchers interested in biomaterials for orthopaedic applications. .
1. Alumina-titanium bio-composites for orthopedic applications -- 2. Manufacturing and characterization of nickel filled Co-30Cr-4Mo metal alloy for orthopedic applications -- 3. Development of Porous Hydroxyaptite scaffold for Bone Regeneration Applications -- 4. Current challenges and Blooms in 3D printing of biomedical devices -- 5. Development of Biodegradable Mg-Hydroxyapatite scaffold for Bone Tissue Engineering Applications -- 6. Current Advances and Future Pathways of 3-D Printing in Bone Tissue Engineering -- 7. Neurosurgical Bone Grinding -- 8. Surface Modification of metallic biomaterials for enhanced wear, corrosion, and bio-activity for Orthopedic Applications -- 9. Influence of machining induced surface integrity on corrosion resistance of Mg-alloy -- 10. Influence of spark plasma on corrosion behavior of Co-Cr implants -- 11. Fabrication of medical model/ implants -- 12. Surface Modification Approach to Bio-manufacturing: Enhancing Surface Integrity and Bio-mechanical Performance of Implants -- 13. Bioinformatics & Nanotechnology: Current Challenges and Pathways -- 14. Biomaterials in orthopaedics and bone regeneration: Design and Synthesis -- 15. Zinc Powder Mixed Electro-discharge Machining on Magnesium Alloy for Potential Biodegradable Implants Application -- 16. Smart Nano-Biomaterial in Orthopaedic Applications.
Keywords: Biomaterials; Biomedical engineering; Orthopedic surgery; Regenerative medicine; Biomaterials; Biomedical Engineering and Bioengineering; Surgical Orthopedics; Regenerative Medicine and Tissue Engineering